2020
DOI: 10.1002/mop.32546
|View full text |Cite
|
Sign up to set email alerts
|

Optical fiber temperature sensor with insensitive refractive index and strain based on phase demodulation

Abstract: We propose and experimentally demonstrate a temperature sensor based on a suspended-core microstructure optical fiber (SCMF). The sensor is constructed by fusion splicing a piece of SCMF between two up-tapers which act as light beam couplers. The Mach-Zehnder interference (MZI) is formed by the silica core modes and the air cladding modes in the SCMF. The sensitivity of −0.011 rad/ C in the temperature range of 20 C to 90 C is achieved, which is more accurate and stable than conventional wavelength tracking me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…For example, Fu et al proposed a multimode interferometer on the basis of an offset spliced single-mode fiber (SMF) structure with temperature and strain sensitivities of only −0.026 rad/°C and 0.0003 rad/με, respectively [14]. Nan et al used a suspended-core microstructure optical fiber sensor for temperature measurement with a low sensitivity of −0.011 rad/°C on the basis of phase demodulation [19]. Galarza et al proposed a new liquid-level sensor multiplexed system on the basis of multimode interference microfibers with a sensitivity of 11.4 rad/mm [20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Fu et al proposed a multimode interferometer on the basis of an offset spliced single-mode fiber (SMF) structure with temperature and strain sensitivities of only −0.026 rad/°C and 0.0003 rad/με, respectively [14]. Nan et al used a suspended-core microstructure optical fiber sensor for temperature measurement with a low sensitivity of −0.011 rad/°C on the basis of phase demodulation [19]. Galarza et al proposed a new liquid-level sensor multiplexed system on the basis of multimode interference microfibers with a sensitivity of 11.4 rad/mm [20].…”
Section: Introductionmentioning
confidence: 99%
“…Lei et al, demonstrated an optical fiber temperature sensor based on a dual-loop optoelectronic oscillator (OEO) with the Vernier effect by using slightly different lengths of single mode fiber [10]. Besides, there are various optical fiber structures designed for temperature measurement [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%